The Daily Gater 24 April 1969 - San Francisco State University - Associated Students (San Francisco State University - Associated Students, 1969)
The Gater for the Fall 1966 - Feb 1972 was published daily during the regular academic year and weekly during the summer by the Board of Publications for the Associated Students of San Francisco State College. This student newspaper was edited by Diran Karaguezian with managing editor Dave Richmond, city editor Greg de Giere, and photo editor Hank Smith. The Daily Gater spotlighted campus news and events and includes advertisements. Best copy available